Formulation and Antioxidant Activity Test of Phycocyanin Phytosomal Gel from Green Algae Extract (Spirulina platensis) - Adela, Nita; Kartika Sari, Untia; Damayanti Abdul Karim, Dewi; Ratnasari, Devi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Green algae (Spirulina platensis) contains phycocyanins are useful as natural antioxidants. Spirulina platensis extract in phytosome gel preparation intended to increase sorption efficiency, physical stability and antioxidant activity. The purpose of this study was to examine the effect of variations ratio of extract to soy lecithin on phytosome characteristics, addition of phytosomes to gel characteristics, and efficiency of sorption on the IC50 of the gel. Extraction of Spirulina platensis using maceration. Optimization of the phytosome formula was carried out with ratio of extract to lecithin, 1:1, 1:2, 1:3. Evaluation of phytosomes showed spherical vesicles, particle size 627.9 nm, polydispersity index 0.382, absorption efficiency of 94%, 95%, 96%. Physical evaluation of the gel showed good results in organoleptic, homogeneous, pH in range 6.3-6.4, viscosity in range 3896-3992 cPs, spreadability in range 6-6.5 cm, stickiness in range 5-6 seconds. Based on results of the irritation test, there was no irritation in each formula. The results of the physical stability test for 6 cycles at 4°C and 40°C showed all formulas had stable in all evaluation results except a decreasing pH. The IC50 results of Spirulina platensis extract and phytosome gel 6.53 µg/mL and 21.59 µg/mL are classified as super strength antioxidant category.